2015
DOI: 10.1039/c5mh00154d
|View full text |Cite
|
Sign up to set email alerts
|

A dopant-free spirobi[cyclopenta[2,1-b:3,4-b′]dithiophene] based hole-transport material for efficient perovskite solar cells

Abstract: A new spiro-cyclopentadithiophene-based hole transport material has been developed for perovskite solar cells exhibiting an excellent power conversion efficiency of 13.4% without the use of any additives and dopants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(91 citation statements)
references
References 52 publications
4
86
0
1
Order By: Relevance
“…Grätzel and co-workers have developed 4,4′-spirobi[cyclopenta[2,1-b:3,4-b′]dithiophene] derivatives, silolothiophene linked methoxy triphenylamines, conjugated quinolizino acridine derivative and S,N-heteroacene-based oligothiophenes as the HTMs without dopants to get a PCE of 10-13%. [7][8][9][10] Other TPA-based HTMs without dopants applied in the PSC have been synthesized by Li and co-workers obtaining PCEs of 11-13%. [11][12][13][14] Yang and co-workers demonstrated efficient planar perovskite solar cells using two dopant-free donor-acceptor conjugated small molecules as hole-transport materials.…”
Section: Doi: 101002/aenm201600401mentioning
confidence: 99%
“…Grätzel and co-workers have developed 4,4′-spirobi[cyclopenta[2,1-b:3,4-b′]dithiophene] derivatives, silolothiophene linked methoxy triphenylamines, conjugated quinolizino acridine derivative and S,N-heteroacene-based oligothiophenes as the HTMs without dopants to get a PCE of 10-13%. [7][8][9][10] Other TPA-based HTMs without dopants applied in the PSC have been synthesized by Li and co-workers obtaining PCEs of 11-13%. [11][12][13][14] Yang and co-workers demonstrated efficient planar perovskite solar cells using two dopant-free donor-acceptor conjugated small molecules as hole-transport materials.…”
Section: Doi: 101002/aenm201600401mentioning
confidence: 99%
“…9 Also, the lack of crystalline spiro-OMeTAD, in particular single crystals prepared in a controlled manner, prevents access to the intrinsic holetransport properties of spiro-OMeTAD, the understanding of which is important for improving performance [10][11][12] and/or developing alternative organic HTMs. [13][14][15] Very recently, significant experimental progress was made in preparing crystalline spiro-OMeTAD. Ganesan et al reported the first crystal structure of a spiro-OMeTAD complex in which, however, chlorobenzene solvent molecules are also embedded.…”
Section: Introductionmentioning
confidence: 99%
“…25 However, apart from a few exceptions, 25,29 most PSCs based on thiophene HTMs show a PCE lower than 16%. [35][36][37][38][39][40][41][42] Herein, we report the synthesis and characterization as well as the application in perovskite solar cells of two novel thiophene-based HTMs, coded Z25 and Z26. The latter is derived by introdution of two double bonds into Z25 as shown in Figure 1a.…”
mentioning
confidence: 99%